Cellulose and hemicellulose decomposition by forest soil bacteria proceeds by the action of structurally variable enzymatic systems - López-Mondéjar, Rubén; Zühlke, Daniela; Becher, Dörte; Riedel, Katharina; Baldrian, Petr (Scientific reports, 2016)
Evidence shows that bacteria contribute actively to the decomposition of cellulose and hemicellulose in forest soil; however, their role in this process is still unclear. Here we performed the screening and identification of bacteria showing potential cellulolytic activity from litter and organic soil of a temperate oak forest. The genomes of three cellulolytic isolates previously described as abundant in this ecosystem were sequenced and their proteomes were characterized during the growth on plant biomass and on microcrystalline cellulose. Pedobacter and Mucilaginibacter showed complex enzymatic systems containing highly diverse carbohydrate-active enzymes for the degradation of cellulose and hemicellulose, which were functionally redundant for endoglucanases, β-glucosidases, endoxylanases, β-xylosidases, mannosidases and carbohydrate-binding modules. Luteibacter did not express any glycosyl hydrolases traditionally recognized as cellulases. Instead, cellulose decomposition was likely performed by an expressed GH23 family protein containing a cellulose-binding domain. Interestingly, the presence of plant lignocellulose as well as crystalline cellulose both trigger the production of a wide set of hydrolytic proteins including cellulases, hemicellulases and other glycosyl hydrolases. Our findings highlight the extensive and unexplored structural diversity of enzymatic systems in cellulolytic soil bacteria and indicate the roles of multiple abundant bacterial taxa in the decomposition of cellulose and other plant polysaccharides.
Keywords: Bacterial Proteins; Cellulose; hydrolýza; Hydrolysis; Soil Microbiology; genom bakteriální; bakteriální proteiny; Quercus; Polysaccharides; Forests; sekvenční analýza DNA; Genome, Bacterial; celulosa; Proteome; polysacharidy; dub (rod); Bacteria; proteom; půdní mikrobiologie; Sequence Analysis, DNA; lesy